Insights into the influence of physicochemical parameters on the microbial community and volatile compounds during the ultra-long fermentation of compound-flavor Baijiu - Cheng, Wei; Chen, Xuefeng; Lan, Wei; Liu, Gengdian; Xue, Xijia; Li, Ruilong; Pan, Tianquan; Li, Na; Zhou, Duan; Chen, Xingjie (Frontiers in Microbiology, 2023)
Changes in physicochemical parameters, microbial communities, metabolism, composition, and the proportion of volatile components in fermented grains (FG) affect Baijiu quality during fermentation.In this study, amplicon sequencing was used to analyze the microbial community, and headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) was used to analyze the volatile components in FG during ultra-long fermentation of compound-flavor Baijiu (CFB). The relationships between the dominant microbial communities, physicochemical parameters, and volatile components were analyzed using redundancy analysis and network analysis. During ultra-long fermentation, bacterial diversity was initially higher than during the mid and late stages.Fungal diversity in the mid stages was higher than that initially and later in the process. A total of 88 volatile components, including six alcohols, 43 esters, eight aldehydes and ketones, 13 acids, and 18 other compounds were detected in FG. Starch and reducing sugars in FG strongly affected the composition and function of bacterial and fungal communities. However, acidity had little effect on the composition and function of the bacterial flora. Lactobacillus, Bacillus, Weissella, and Pichia were the core microbial genera involved in metabolizing the volatile components of FG. We provide insights into the relationships and influences among the dominant microbial communities, physicochemical parameters, and volatile components during ultra-long fermentation of CFB. These insights help clarify the fermentation mechanisms of solid-state fermentation Baijiu (SFB) and control and improve the aroma quality of CFB.